2021
DOI: 10.3390/md19020062
|View full text |Cite
|
Sign up to set email alerts
|

Limited Benefit of Marine Protein Hydrolysate on Physical Function and Strength in Older Adults: A Randomized Controlled Trial

Abstract: Age-related muscle wasting can compromise functional abilities of the elderly. Protein intake stimulates muscle protein synthesis; however, ageing muscle is more resistant to stimuli. This double-blinded, randomized, controlled trial is one of the first registered studies to evaluate the effects of a supplement of marine protein hydrolysate (MPH) on measures of physical function and strength. Eighty-six older adults received nutritional supplements containing 3 g of MPH or a placebo for up to 12 months. Short … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Concerning fish proteins, Nygard et al [ 43 ] aimed to demonstrate the benefits of cod peptides in older adults (n = 86, mean age of 73 years old) who ingested 3 g for a year. Parameters such as short physical performance battery, grip strength, gait speed, and dietary intake were considered, but at the end of the study, authors reported no significant differences observed after the test item ingestion.…”
Section: In Vivo Studies: Description Of Resultsmentioning
confidence: 99%
“…Concerning fish proteins, Nygard et al [ 43 ] aimed to demonstrate the benefits of cod peptides in older adults (n = 86, mean age of 73 years old) who ingested 3 g for a year. Parameters such as short physical performance battery, grip strength, gait speed, and dietary intake were considered, but at the end of the study, authors reported no significant differences observed after the test item ingestion.…”
Section: In Vivo Studies: Description Of Resultsmentioning
confidence: 99%
“…Marine peptides are approved as a food ingredient in Norway. The peptide compounds are manufactured by hydrolysis of the Atlantic cod Gadus morhua fillet [ 30 ]. The tablets are produced by Flexipharma AS and based on the marine peptide compound 565952 P from Firmenich Bjørge Biomarin AS.…”
mentioning
confidence: 99%
“…This is one of the first long-term studies of MPH and age-related changes in muscle health. Despite a limited benefit of marine protein hydrolysate on physical function and strength in older adults was delivered, the authors came to the conclusion that a daily intake of 3 g MPH for 6 to 12 months would prevent loss of physical performance, compared with a placebo [ 30 ].…”
mentioning
confidence: 99%